Making Things and Drawing Boundaries Experiments in the Digital Humanities - Sayers, Jentery (University of Minnesota Press, 2017)
In Making Things and Drawing Boundaries, critical theory and cultural practice meet creativity, collaboration, and experimentation with physical materials as never before. Foregrounding the interdisciplinary character of experimental methods and hands-on research, this collection asks what it means to "make" things in the humanities. How is humanities research manifested in hand and on screen alongside the essay and monograph? And, importantly, how does experimentation with physical materials correspond with social justice and responsibility? Comprising almost forty chapters from ninety practitioners across twenty disciplines, Making Things and Drawing Boundaries speaks directly and extensively to how humanities research engages a growing interest in "maker" culture, however "making" may be defined. Contributors: Erin R. Anderson; Joanne Bernardi; Yana Boeva; Jeremy Boggs; Duncan A. Buell; Amy Burek; Trisha N. Campbell; Debbie Chachra; Beth Compton; Heidi Rae Cooley; Nora Dimmock; Devon Elliott; Bill Endres; Katherine Faull; Alexander Flamenco; Emily Alden Foster; Sarah Fox; Chelsea A. M. Gardner; Susan Garfinkel; Lee Hannigan; Sara Hendren; Ryan Hunt; John Hunter; Diane Jakacki; Janelle Jenstad; Edward Jones-Imhotep; Julie Thompson Klein; Aaron D. Knochel; J. K. Purdom Lindblad; Kim Martin; Gwynaeth McIntyre; Aurelio Meza; Shezan Muhammedi; Angel David Nieves; Marcel O'Gorman; Amy Papaelias; Matt Ratto; Isaac Record; Jennifer Reed; Gabby Resch; Jennifer Roberts-Smith; Melissa Rogers; Daniela K. Rosner; Stan Ruecker; Roxanne Shirazi; James Smithies; P. P. Sneha; Lisa M. Snyder; Kaitlyn Solberg; Dan Southwick; David Staley; Elaine Sullivan; Joseph Takeda; Ezra Teboul; William J. Turkel; Lisa Tweten.